2017
DOI: 10.1073/pnas.1703668114
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurons multiplex reward-related signals along with sensory and motor information

Abstract: Rewards are known to influence neural activity associated with both motor preparation and execution. This influence can be exerted directly upon the primary motor (M1) and somatosensory (S1) cortical areas via the projections from reward-sensitive dopaminergic neurons of the midbrain ventral tegmental areas. However, the neurophysiological manifestation of reward-related signals in M1 and S1 are not well understood. Particularly, it is unclear how the neurons in these cortical areas multiplex their traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 94 publications
(84 reference statements)
8
68
0
Order By: Relevance
“…Multiple units in M1 have been shown to respond to the conditioned (CS) and unconditioned stimuli (US) (2,(15)(16)(17). We have also reported previously (2) and in Fig.3 that the average activity of M1 is significantly different throughout a rewarding trial with respect to a nonrewarding trial.…”
Section: M1 Units Have Heterogeneous Representations Of Conditioned Asupporting
confidence: 80%
See 2 more Smart Citations
“…Multiple units in M1 have been shown to respond to the conditioned (CS) and unconditioned stimuli (US) (2,(15)(16)(17). We have also reported previously (2) and in Fig.3 that the average activity of M1 is significantly different throughout a rewarding trial with respect to a nonrewarding trial.…”
Section: M1 Units Have Heterogeneous Representations Of Conditioned Asupporting
confidence: 80%
“…Previously we, and others, have shown that reward modulates single units and local field potentials in the primary sensorimotor cortices (M1, S1) of non-human primates (2,(15)(16)(17) and frontal regions influencing M1 (18). We have proposed that neural correlates of reward could be used towards an autonomously updating brain machine interface (2,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally, M1, S1 and dorsal premotor (pMd) neurons in primates increase their firing rates when reward expectation is not met 54,55 . A recent study showed that M1 LFP spectral power in the 8-14 Hz band increased in non-rewarding trials as compared to rewarded trials in a primate center-out reaching task 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological, imaging and lesion studies succeeded in identifying motivation-related and rewardrelated signals in different brain areas [1][2][3] . While prefrontal and parietal cortex seem more involved in encoding the value and salience of the sensory signals used to inform about the incoming reward, the activity in motor cortical areas was proposed to be mostly related to the motivation to perform an action 4,5 even if modulated by other factors like reward expectation 6,7 , reward feedback 8 , and anticipation of reward delivery 9 .…”
Section: Introductionmentioning
confidence: 99%